When did the Schism begin, and why? Views on the English Reformation amongst Catholic polemicists - Katy Gibbons (Etudes Epistémè)
For Catholic polemicists, the Break with Rome and the establishment of the Church of England did not signal the arrival of religious truth and renewal, with a clear start date and a point of completion; rather it was a schism, a breaking from the true church. Its dating and origins were intimately connected with the moral failings and lust of Henry VIII. Marian authors were able to reflect on this scenario from the position of an England restored to Catholicism, but they were bookended by those in the reigns of Henry VIII and Elizabeth I, whose explanations of the English Reformation were shaped by their own experience of displacement and dispossession. This article outlines the ways in which the ‘losers’ of the Reformation portrayed the timing and origins of England’s schism to their fellow English Catholics, and to the wider Catholic world. The potential of their narrative to puncture the myth of inevitable Protestant triumph was such that Protestant regimes in England were eager to take action against writers and their work. For contemporaries, this was not just an academic exercise in history writing; this Catholic version of the Reformation story was intended to spur on action against an illegitimate and heretical regime. Discussion of the timing and reasons for the Break with Rome could thus also be a call to arms.